Impact of Nutritional Health Among Adolescents in Rural India (International Journal of Food and Nutritional Sciences, 2022)
Adolescence is a phase of accelerated development requiring heightened macro- and micronutrient intake. In rural India, adolescents frequently encounter food instability, inadequate dietary diversity, and restricted access to health services. Anemia and undernutrition hinder physical development, cognitive abilities, and attending classes. This study evaluates the dietary status and factors contributing to anemia in rural adolescents. Adolescence (10–19 years) represents a pivotal period for nutritional treatments. This research addresses the nutritional status, dietary diversity, and factors linked to anemia and undernutrition in adolescents residing in rural India. Cross-sectional study including 202 teenagers in rural communities (simulated dataset). socio-demographics, Dietary Diversity Score (DDS; 0–9), anthropometry (BMI-for-age z-score), hemoglobin concentration (g/dL). Analyses: descriptive statistics, chi-square tests, t-tests, Spearman correlation In this simulated rural adolescent cohort, female adolescents exhibited increased probabilities of anemia. Dietary diversity (DDS) exhibited no significant correlation with anemia in the adjusted model. It is advised to concentrate programmatic efforts on adolescent girls, specifically regarding iron supplements, school-based nutrition, and menstrual health counseling.